Factors influencing internet addiction among university students in Malaysia: a review of the literature - Muhammad Amirul Zaidi,; Nurzahirah Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Internet addiction is an increasing public concern, especially among university students. Excessive Internet use for social networking, online gaming, and browsing is a defining feature of this issue. It can interfere with social connections, mental health, and academic achievement. Due to their increased access to digital devices, social networking, and online entertainment, university students in Malaysia are susceptible to this addiction. Internet addiction is on the rise due to several factors, including peer pressure, social isolation, academic pressure, and mental health issues. The drive for social approval and the normalization of excessive Internet use through sites like social networking and competitive gaming exacerbate the issue significantly. Majority of the university students in Malaysia display at least mild symptoms of Internet addiction. They find it challenging to strike a balance between their academic obligations and their leisure online activities due to the ubiquitous availability of the Internet via smartphones and campus networks. Existing studies on Internet addiction among university students in Malaysia have explored psychological, social, behavioral, and technological factors, often in isolation. However, there is a gap in exploring the integrated impact of these factors and their coexistence within the university context. Hence, this study aims to provide a comprehensive review of these contributing factors among university students in Malaysia. Universities should take some initiatives to introduce digital literacy workshops, digital detox programs, and peer support groups to combat this issue. In the digital age, these initiatives will support improved mental health, academic achievement, and general well-being.